Badania ankietowe – analiza, wyniki i rekomendacje ………. 163 - Solarz, Katarzyna (Wybory prezydenckie w Polsce w 2025 roku w świadomości najmłodszego elektoratu województwa małopolskiego, 2025)
SURVEY RESEARCH – ANALYSIS, RESULTS, AND RECOMMENDATIONSThis chapter presents the results of a survey-based study conducted among adult students attending selected secondary schools in the Lesser Poland Voivodeship. The analysis focuses on students’ knowledge regarding the constitutional status of the President of the Republic of Poland, the nature and significance of presidential elections, their willingness to participate in such elections, familiarity with candidates, and sources of information concerning the electoral process. The findings are examined in relation to respondents’ gender, type of school attended, and the population size of the locality where the school is situated. Most of the research hypotheses have been confirmed. The level of knowledge demonstrated by secondary school students can be considered satisfactory, and the respondents generally declare an intention to engage in electoral participation. Students attending general secondary schools and those from schools located in Kraków exhibit higher levels of knowledge compared to students from vocational schools and smaller urban areas. Notably, schools are rarely identified as a source of information about elections, which underscores the need to revise and adapt curricular content to better foster political and civic engagement among young people.